A high-strength wear-resistant ABS alloy and preparation method thereof

By using specific proportions and processes in ABS alloy materials, including the compounding of wear-resistant inorganic fillers, toughened and reinforced fibrous fillers and toughened and reinforced whisker fillers, as well as TPU tougheners and surface The modification process solves the problems of insufficient strength, impact toughness and wear resistance of ABS alloy materials, and realizes high-strength and wear-resistant ABS alloy materials.

CN118530574BActive Publication Date: 2025-01-17DONGGUAN YUJIE IND INVESTMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410647689.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-01-17
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The overall strength of existing ABS alloy materials is poor, impact toughness and wear resistance are weak.

Method used

Use 70-80 parts of PC resin, 14-20 parts of ABS resin, 4-8 parts of toughening agent, 18-26 parts of inorganic filler composition with wear-resistant, toughening and reinforcing effects, 0.5-2 parts of The proportion of coupling agent, 0.5-2 parts of dispersant, 3-6 parts of compatibilizer, and 0.5-2 parts of anti-aging agent is used to prepare high-strength wear-resistant ABS alloy through a twin-screw extrusion process.

Benefits of technology

It significantly improves the anti-aging performance, wear resistance, mechanical strength, impact toughness and low-temperature resistance of ABS alloy materials, and solves the problem of high residual stress in molding and easy stress cracking of products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004855359350000191
    Figure BDA0004855359350000191
  • Figure BDA0004855359350000201
    Figure BDA0004855359350000201
Patent Text Reader

Abstract

The present invention relates to the technical field of ABS alloy materials, in particular to a high-strength wear-resistant ABS alloy and a preparation method thereof. A high-strength wear-resistant ABS alloy comprises the following raw materials in parts by weight: 70-80 parts of PC resin, 14-20 parts of ABS resin, 4-8 parts of toughening agent, 18-26 parts of inorganic filler composition with wear-resistant toughening and reinforcing effect, 0.5-2 parts of coupling agent, 0.5-2 parts of dispersant, 3-6 parts of compatibilizer, 0.5-2 parts of anti-aging agent; the inorganic filler composition with wear-resistant toughening and reinforcing effect comprises wear-resistant inorganic filler, toughening and reinforcing fibrous filler, toughening and reinforcing whisker filler with a mass ratio of (8-15): (75-88): (4-10). The high-strength wear-resistant ABS alloy obtained by the present invention has good wear resistance and mechanical strength while having good impact toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ABS alloy materials, and in particular to a high-strength wear-resistant ABS alloy and a preparation method thereof. Background Art

[0002] Polycarbonate PC has good mechanical properties, heat resistance and excellent impact toughness. It is a non-crystalline engineering plastic with a transparent appearance and excellent comprehensive performance. It is widely used in machinery, automobiles, electronic appliances, packaging materials and other technical fields. Although polycarbonate PC has excellent performance in some aspects, it contains polar ester groups and the molecular chain is relatively rigid, resulting in its rigidity but poor flexibility. The high melting point leads to poor extrusion processing performance. In addition, polycarbonate PC has poor fluidity, which makes it difficult to manufacture large thin-walled products, and the residual stress after molding is large, and the product is prone to stress cracking.

[0003] ABS resin is made by grafting polybutadiene rubber (PB), styrene (S) and acrylonitrile (A), in which polybutadiene rubber PB gives ABS resin good overall thermal stability, acrylonitrile S gives ABS resin good overall toughness and impact resistance, and styrene S gives ABS resin good overall rigidity and processability. Although ABS resin has excellent overall performance, high impact strength at low temperatures, and good dimensional stability, it is also one of the widely used engineering plastics. However, compared with polycarbonate PC, it can be seen that ABS resin has the advantages of good molding and low cost, but its disadvantages are relatively poor impact toughness and heat resistance. In order to improve the impact toughness and heat resistance of ABS resin, polycarbonate PC is usually used to modify ABS resin. PC / ABS alloy material. PC / ABS alloy material has the excellent properties of both polycarbonate PC and ABS resin, making it widely used in automotive interior parts, communication equipment, household appliances, lighting equipment and other scenes.

[0004] At present, the ABS alloy material in the prior art includes PC resin, ABS resin, toughening agent MBS, short glass fiber, dispersant, and antioxidant. The mass ratio of PC resin to ABS resin is (12-16): (60-70); the content of toughening agent MBS is 3-8wt%; the content of short glass fiber is 15-20wt%, the content of dispersant is 0.1-2.0wt%, and the content of antioxidant is 0.5-1.0wt%. The tensile strength of the prepared ABS alloy material is 60-85MPa, the bending strength is 60-100MPa, and the notched impact strength is 4-12KJ / m 2 , the elongation at break is 3-8%, and the loss is 180-250mm.

[0005] With respect to the ABS alloy materials in the above-mentioned related art, the applicant has found that the overall strength of the existing ABS alloy materials is unsatisfactory, the impact toughness is relatively poor and the overall wear resistance is also weak. To this end, the present invention provides a high-strength wear-resistant ABS alloy and a preparation method thereof. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a high-strength and wear-resistant ABS alloy and a preparation method thereof.

[0007] The high-strength wear-resistant ABS alloy provided by the present invention is realized by the following technical solutions:

[0008] A high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 70-80 parts of PC resin, 14-20 parts of ABS resin, 4-8 parts of toughening agent, 18-26 parts of inorganic filler composition with wear-resistant, toughening and reinforcing effects, 0.5-2 parts of coupling agent, 0.5-2 parts of dispersant, 3-6 parts of compatibilizer, and 0.5-2 parts of anti-aging agent;

[0009] The inorganic filler composition with wear-resistant, toughening and reinforcing effects comprises a wear-resistant inorganic filler, a toughening and reinforcing fibrous filler and a toughening and reinforcing whisker-like filler in a mass ratio of (8-15):(75-88):(4-10); the wear-resistant inorganic filler is spherical alumina and / or spherical silicon carbide with at least one of ultrafine mica sheets and boron nitride nanosheets; the toughening and reinforcing fibrous filler is chopped ceramic fiber with at least one of nano-aramid fiber, nano-carbon fiber and chopped aramid fiber;

[0010] The toughening and reinforcing whisker-like filler is zinc oxide whisker and / or potassium titanate whisker;

[0011] The toughening agent is TPU resin;

[0012] The coupling agent is siloxane and / or titanate coupling agent;

[0013] The dispersant is stearate;

[0014] The compatibilizer is ABS-g-MAH and / or styrene-grafted maleic anhydride multipolymer;

[0015] The anti-aging agent is composed of an antioxidant and an anti-ultraviolet agent in a mass ratio of (1-2):(1-2).

[0016] The inorganic filler composition formed by compounding wear-resistant inorganic fillers, toughening and reinforcing fibrous fillers and toughening and reinforcing whisker-like fillers in the present invention gives the ABS alloy material good anti-aging performance, wear resistance and mechanical strength, while also having good impact toughness and low-temperature resistance, thereby solving the problem of large residual stress in molding and easy stress cracking of products.

[0017] Preferably, the high-strength and wear-resistant ABS alloy is made of the following raw materials in parts by weight: 80 parts of PC resin, 18-20 parts of ABS resin, 5-6 parts of toughening agent, 22-24 parts of an inorganic filler composition with wear-resistant, toughening and reinforcing effects, 1-2 parts of a coupling agent, 1-2 parts of a dispersant, 4-6 parts of a compatibilizer, and 1-2 parts of an anti-aging agent.

[0018] Preferably, the inorganic filler composition with wear-resistant, toughening and reinforcing effects comprises a wear-resistant inorganic filler, a toughening and reinforcing fibrous filler and a toughening and reinforcing whisker filler in a mass ratio of 10:85:5; the wear-resistant inorganic filler is spherical alumina, ultrafine mica flakes and boron nitride nanosheets in a mass ratio of (70-90):(5-20):(5-10); the toughening and reinforcing whisker filler is zinc oxide whisker and potassium titanate whisker in a mass ratio of (40-60):(40-60).

[0019] By optimizing the ratio of wear-resistant inorganic fillers, toughening and reinforcing fibrous fillers, and toughening and reinforcing whisker fillers, the anti-aging properties, wear resistance, mechanical strength, impact toughness and low-temperature resistance of ABS alloy materials can be improved.

[0020] Preferably, the toughening and reinforcing fibrous filler is composed of chopped ceramic fibers, nano-carbon fibers, and chopped aramid fibers in a mass ratio of (50-85):(5-10):(10-40); the chopped ceramic fibers include chopped ceramic fibers with a length of 0.5-2.0 mm, chopped ceramic fibers with a length of 4-8 mm, and chopped ceramic fibers with a length of 10-15 mm; the length of the chopped aramid fibers is 0.5-15.0 mm.

[0021] By optimizing the ratio of chopped ceramic fibers, nanocarbon fibers and chopped aramid fibers, the anti-aging properties, wear resistance, mechanical strength, impact toughness and low-temperature resistance of ABS alloy materials can be improved.

[0022] Preferably, the toughening and reinforcing fibrous filler is composed of chopped ceramic fibers, nano-aramid fibers, and chopped carbon fibers in a mass ratio of (50-85):(5-10):(10-40); the chopped ceramic fibers include chopped ceramic fibers with a length of 0.5-2.0 mm, chopped ceramic fibers with a length of 4-8 mm, and chopped ceramic fibers with a length of 10-15 mm; the length of the chopped carbon fibers is 0.5-8.0 mm.

[0023] By optimizing the ratio of chopped ceramic fiber, nano-aramid fiber and chopped carbon fiber, the anti-aging performance, wear resistance, mechanical strength, impact toughness and low-temperature resistance of ABS alloy materials can be improved.

[0024] Preferably, the mass ratio of the chopped ceramic fibers with a length of 0.5-2.0 mm, the chopped ceramic fibers with a length of 4-8 mm, and the chopped ceramic fibers with a length of 10-15 mm in the chopped ceramic fibers is (10-20):(60-80):(10-20).

[0025] By optimizing the ratio of short-cut ceramic fibers of different lengths, the overall production cost can be reduced while ensuring that the ABS alloy material has good anti-aging performance, wear resistance, mechanical strength, impact toughness and low-temperature resistance.

[0026] Preferably, the TPU resin comprises diisocyanate, a small molecule diol chain extender, a polyol, a catalyst, a wear-resistant filler, a leveling agent, an antioxidant, and a UV absorber; the total molar amount of the active functional groups contained in the chain extender and the polyol is equal to 1.0-1.02 times the molar amount of -NCO in the diisocyanate; the hard segment content in the TPU resin is 45-50wt%; the diisocyanate is an aromatic diisocyanate or a combination of an aromatic diisocyanate and an aliphatic diisocyanate; the small molecule diol chain extender is 1,4-butanediol, 3-methyl-1,5-pentanediol At least one of alcohol, 1,6-hexanediol, 1,4-butanediamine, and 1,6-hexanediamine; the polyol is composed of terminal hydroxyl polybutadiene with a molecular weight of 500-2000, polycarbonate diol with a molecular weight of 1000-2000, and hydroxyl-terminated methyl vinyl silicone oil with a vinyl content of 6-8 mol% in a mass ratio of (10-30):(60-85):(5-10); the catalyst is organic tin or organic bismuth; the wear-resistant filler content in the TPU resin is 2-4wt%; the wear-resistant filler is at least one of nano-alumina, nano-zirconium oxide, and nano-tungsten carbide.

[0027] The self-made TPU resin in the present invention can effectively improve the impact toughness and low-temperature resistance of the ABS alloy material.

[0028] Preferably, the coupling agent is composed of a siloxane coupling agent and a titanate coupling agent in a mass ratio of (80-90):(10-20); the siloxane coupling agent includes methacryloxysilane and aminosilane, which are prepared by reflux reaction at 70-90°C for 2-4h; the titanate coupling agent is di(dioctylpyrophosphoryl)ethylene titanate and / or di(dioctylpyrophosphoryl)oxyacetyl peptide.

[0029] By adopting the above technical solution, the inorganic filler composition with wear-resistant, toughening and reinforcing effect after the surface treatment of the above coupling agent can be evenly dispersed in the PC resin and ABS resin matrix, thereby ensuring that the ABS alloy has good anti-aging performance, wear resistance, mechanical strength, and good impact toughness and low temperature resistance.

[0030] Preferably, the antioxidant is composed of an antioxidant and an anti-ultraviolet agent in a mass ratio of (1.4-1.6):(0.8-1.2); the antioxidant is at least one of nano-silicon nitride, nano-silicon dioxide, and nano-titanium nitride in combination with antioxidant 1098 and antioxidant 168; the anti-ultraviolet agent is at least one of UV-531, UV-326, UV-327, UV-328, UV-329, UV-234, and UV-770.

[0031] By adopting the above technical solution, the anti-aging and anti-ultraviolet aging properties and high temperature processing properties of ABS alloy can be improved.

[0032] The present invention provides a method for preparing a high-strength wear-resistant ABS alloy, which is achieved through the following technical solutions:

[0033] A method for preparing a high-strength wear-resistant ABS alloy comprises the following steps:

[0034] Step 1: Preparation of an inorganic filler composition having wear-resistant, toughening and reinforcing effects and preparation of a toughening agent;

[0035] Step 2: using a coupling agent to perform surface modification treatment on the inorganic filler composition having wear-resistant, toughening and reinforcing effects;

[0036] Step three, the accurately measured PC resin, ABS resin, toughening agent, surface modified inorganic filler composition with wear-resistant toughening and reinforcing effect, coupling agent, dispersant, compatibilizer and antioxidant are mixed at high speed and then put into a twin-screw extruder, and melt extrusion is carried out at an extrusion temperature of 245-255°C and a screw speed of 300-500rpm. The obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain PC / ABS alloy masterbatch material.

[0037] The preparation method provided by the present invention is relatively simple, has low difficulty in implementation, and is easy to implement for industrial production.

[0038] In summary, the present invention has the following advantages:

[0039] 1. The present invention has good anti-aging performance, wear resistance, mechanical strength, and good impact toughness and low-temperature resistance, solving the problem of large residual stress in molding and easy stress cracking of products.

[0040] 2. The preparation method provided by the present invention is relatively simple, has low difficulty in implementation, and is easy to implement in industrial production. DETAILED DESCRIPTION

[0041] In order to further understand the technical solution of the present invention, the preferred implementation scheme is described below in conjunction with examples and comparative examples.

[0042] Preparation Example

[0043] Preparation Example 1: Toughener TPU resin is prepared from the following materials: 450.7g of diisocyanate MDI, 33.64g of diisocyanate HDI, 118.17g of 1,6-hexanediol, 67.34g of 3-methyl-1,5-pentanediol, 266g of hydroxy-terminated polybutadiene with a number average molecular weight of 1900 (NISSO-PB G-2000 from Soda, Japan), 520g of polycarbonate diol with a molecular weight of 2000 (PCDL1022 Polycarbonatediol, Haoyi New Materials), 15g of hydroxy-terminated methyl vinyl silicone oil (IOTA 1203V, measured vinyl content: 7mol%, hydroxyl content: 6.8%), 30g nano zirconium oxide (HN-R30 nano zirconium dioxide from Chaotai Metal Materials, Qinghe County, CAS No. 1455-6-8, average particle size 30nm), 0.8g catalyst-bismuth octanoate, 8g antioxidant 1010, 2g antioxidant 168, 8g ultraviolet absorber UV-531, 20g leveling agent TEGO Glide 100. The hard segment content in the TPU resin is controlled to be 45.5wt%.

[0044] The preparation method of the toughening agent TPU resin is as follows, comprising the following steps:

[0045] Step 1: Feeding:

[0046] 118.17 g of 1,6-hexanediol and 67.34 g of 3-methyl-1,5-pentanediol were added to the first feed tank of the twin-screw extruder;

[0047] 266 g of hydroxy-terminated polybutadiene (NISSO-PB G-2000) with a number average molecular weight of 1900, 520 g of polycarbonate diol (PCDL1022) with a molecular weight of 2000, and 15 g of hydroxy-terminated methyl vinyl silicone oil (IOTA 1203V, measured vinyl content: 7 mol%, hydroxyl content: 6.8%) were put into the second feed tank of the twin-screw extruder;

[0048] 450.7 g of diisocyanate MDI, 33.64 g of diisocyanate HDI, 0.8 g of catalyst-bismuth octanoate, 8 g of antioxidant 1010, 2 g of antioxidant 168, 8 g of ultraviolet absorber UV-531, 20 g of leveling agent TEGO Glide 100, and 30 g of nano zirconium oxide were mixed evenly and then put into the third feed tank of the twin-screw extruder;

[0049] Step 2: extrusion granulation. The temperature range of the metering section in the twin-screw extruder is 185°C, the temperature range of the compression section is 175°C, the temperature range of the feed section is 182°C, the die head temperature is 190.5°C, the screw speed is 30rpm, and a gear pump is used to discharge the material from the twin-screw extruder, extrude, water-cool, and granulate to obtain semi-finished TPU pellets. The semi-finished TPU pellets are placed at 85.0°C, dried to a moisture content of less than 0.02%, and then heat treated at 80.0°C for 24 hours to obtain finished TPU resin pellets.

[0050] The difference between Preparation Example 2 and Preparation Example 1 is that the toughening agent TPU resin is prepared from the following substances: 450.7g of diisocyanate MDI, 33.64g of diisocyanate HDI, 118.17g of 1,6-hexanediol, 73.27g of 3-methyl-1,5-pentanediol, 152g of hydroxy-terminated polybutadiene with a number average molecular weight of 1900 (Japan Soda NISSO-PB G-2000), 560g of polycarbonate diol with a molecular weight of 2000 (PCDL1022 Polycarbonatediol, Haoyi New Materials), 10g of hydroxy-terminated methyl vinyl silicone oil (IOTA 1203V, measured vinyl content: 7mol%, hydroxyl content: 6.8%), 30g nano zirconium oxide (HN-R30 nano zirconium dioxide from Chaotai Metal Materials, Qinghe County, CAS No. 1455-6-8, average particle size 30nm), 0.8g catalyst-bismuth octanoate, 8g antioxidant 1010, 2g antioxidant 168, 8g ultraviolet absorber UV-531, 20g leveling agent TEGO Glide 100. The hard segment content in the TPU resin is controlled to be 48.3wt%.

[0051] The difference between Preparation Example 3 and Preparation Example 1 is that the toughening agent TPU resin is prepared from the following substances: 450.7g of diisocyanate MDI, 33.64g of diisocyanate HDI, 118.17g of 1,6-hexanediol, 75.63g of 3-methyl-1,5-pentanediol, 161.5g of hydroxy-terminated polybutadiene with a number average molecular weight of 1900 (Japan Soda NISSO-PB G-2000), 510g of polycarbonate diol with a molecular weight of 2000 (PCDL1022 Polycarbonatediol, Haoyi New Materials), 10g of hydroxy-terminated methyl vinyl silicone oil (IOTA 1203V, measured vinyl content: 7mol%, hydroxyl content: 6.8%), 30g nano zirconium oxide (HN-R30 nano zirconium dioxide from Chaotai Metal Materials, Qinghe County, CAS No. 1455-6-8, average particle size 30nm), 0.8g catalyst-bismuth octanoate, 8g antioxidant 1010, 2g antioxidant 168, 8g ultraviolet absorber UV-531, 20g leveling agent TEGO Glide 100. The hard segment content in the TPU resin is controlled to be 49.9wt%.

[0052] The difference between Preparation Example 4 and Preparation Example 1 is that the toughening agent TPU resin is prepared from the following substances: 450.7g of diisocyanate MDI, 33.64g of diisocyanate HDI, 118.17g of 1,6-hexanediol, 82.72g of 3-methyl-1,5-pentanediol, 114g of hydroxy-terminated polybutadiene with a number average molecular weight of 1900 (Japan Soda NISSO-PB G-2000), 440g of polycarbonate diol with a molecular weight of 2000 (PCDL1022 Polycarbonatediol, Haoyi New Materials), 10g of hydroxy-terminated methyl vinyl silicone oil (IOTA 1203V, measured vinyl content: 7 mol%, hydroxyl content: 6.8%), 30g nano zirconium oxide (HN-R30 nano zirconium dioxide from Chaotai Metal Materials, Qinghe County, CAS No. 1455-6-8, average particle size 30nm), 0.8g catalyst-bismuth octanoate, 8g antioxidant 1010, 2g antioxidant 168, 8g ultraviolet absorber UV-531, 20g leveling agent TEGO Glide 100. The hard segment content in the TPU resin is controlled to be 54.8wt%.

[0053] The difference between Preparation Example 5 and Preparation Example 1 is that the toughening agent TPU resin is prepared from the following substances: 450.7g of diisocyanate MDI, 33.64g of diisocyanate HDI, 118.17g of 1,6-hexanediol, 60.27g of 3-methyl-1,5-pentanediol, 171g of hydroxy-terminated polybutadiene with a number average molecular weight of 1900 (Japan Soda NISSO-PB G-2000), 720g of polycarbonate diol with a molecular weight of 2000 (PCDL1022 Polycarbonatediol, Haoyi New Materials), 20g of hydroxy-terminated methyl vinyl silicone oil (IOTA 1203V, measured vinyl content: 7 mol%, hydroxyl content: 6.8%), 30g nano zirconium oxide (HN-R30 nano zirconium dioxide from Chaotai Metal Materials, Qinghe County, CAS No. 1455-6-8, average particle size 30nm), 0.8g catalyst-bismuth octanoate, 8g antioxidant 1010, 2g antioxidant 168, 8g ultraviolet absorber UV-531, 20g leveling agent TEGO Glide 100. The hard segment content in the TPU resin is controlled to be 42.1wt%.

[0054] Preparation Example 6: The surface modification treatment method of the inorganic filler composition having wear-resistant, toughening and reinforcing effects is as follows:

[0055] Step 1, preparation of composite coupling agent:

[0056] 1 mol of γ-methacryloxypropyltrimethoxysilane KH-570 and 1.02 mol of γ-aminopropyltriethoxysilane KH550 were mixed evenly, and refluxed at 80±1° C. for 4 hours to obtain a siloxane coupling agent. After cooling to room temperature, 2 g of di(dioctylpyrophosphoryl)ethylene titanate was added to 12 g of the obtained siloxane coupling agent, and the mixture was stirred at 30 rpm for 15 min to obtain a composite coupling agent.

[0057] At the same time, an inorganic filler composition with wear-resistant, toughening and reinforcing effects is prepared: 7g of spherical alumina, 7g of ultrafine phlogopite flakes, 110g of chopped ceramic fibers (length 5mm), 6g of nanocarbon fibers, and 7g of zinc oxide whiskers are dispersed at high speed for 4 hours;

[0058] Step 2: Add the inorganic filler composition with wear-resistant, toughening and reinforcing functions to the grinder, and evenly add the composite coupling agent to the grinder through a quantitative pump. 10 g of the composite coupling agent is added to 100 g of the inorganic filler composition with wear-resistant, toughening and reinforcing functions. Grinding is performed during the addition of the composite coupling agent. After the addition of the composite coupling agent is completed, grinding is continued for 15 minutes to obtain a surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions.

[0059] The difference between Preparation Example 7 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 8g of spherical alumina (6250 mesh spherical alumina powder DCA-02S, CAS No. 1344-28-1, Dongguan Dongchao New Materials Technology Co., Ltd.), 8g of ultrafine phlogopite flakes (2000 mesh customized, Wuxi Dingsheng Technology Co., Ltd.), 120g of chopped ceramic fibers (3MNextel 720 ceramic fibers, length 5mm), 16g of nanocarbon fibers (nanocarbon fiber powder, average particle size 100-200nm, Qinghe County Ruijiang Metal Materials Co., Ltd.), and 8g of zinc oxide whiskers (four-needle zinc oxide whiskers XD-ZJX05, CAS No. 1344-2-2, Qinghe County Chaotai Metal Materials Co., Ltd.) are dispersed at high speed for 4h.

[0060] The difference between Preparation Example 8 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 12g of spherical alumina, 12g of ultrafine phlogopite flakes, 180g of chopped ceramic fibers, 24g of nanocarbon fibers, and 12g of zinc oxide whiskers are dispersed at high speed for 4 hours.

[0061] The difference between Preparation Example 9 and Preparation Example 6 is that: an inorganic filler composition with wear-resistant, toughening and reinforcing effects is prepared: 9.6g of spherical alumina, 9.6g of ultrafine phlogopite flakes, 180g of chopped ceramic fibers, 31.2g of nanocarbon fibers, and 9.6g of zinc oxide whiskers are dispersed at high speed for 4 hours.

[0062] The difference between Preparation Example 10 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 18g of spherical alumina, 18g of ultrafine phlogopite flakes, 160g of chopped ceramic fibers, 20g of nanocarbon fibers, and 24g of zinc oxide whiskers are dispersed at high speed for 4 hours.

[0063] The difference between Preparation Example 11 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 16.8g spherical alumina, 4.8g ultrafine phlogopite flakes, 2.4g boron nitride nanosheets (hBN-500nm nanosheets, Suzhou Kaifa New Materials Technology), 180g chopped ceramic fibers, 24g nano-carbon fibers, 6g zinc oxide whiskers, and 6g potassium titanate whiskers (CAS No. 12030-97-6, average particle size 5-10 microns, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.) are dispersed at high speed for 4 hours.

[0064] The difference between Preparation Example 12 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 19.2g of spherical alumina, 2.4g of ultrafine phlogopite flakes, 2.4g of boron nitride nanosheets, 180g of chopped ceramic fibers, 24g of nanocarbon fibers, 6g of zinc oxide whiskers, and 6g of potassium titanate whiskers are dispersed at high speed for 4 hours.

[0065] The difference between Preparation Example 13 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 21.6g of spherical alumina, 1.2g of ultrafine phlogopite flakes, 1.2g of boron nitride nanosheets, 180g of chopped ceramic fibers, 24g of nanocarbon fibers, 6g of zinc oxide whiskers, and 6g of potassium titanate whiskers are dispersed at high speed for 4 hours.

[0066] The difference between Preparation Example 14 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 8g of spherical alumina, 8g of ultrafine phlogopite flakes, 8g of boron nitride nanosheets, 180g of chopped ceramic fibers, 24g of nanocarbon fibers, 6g of zinc oxide whiskers, and 6g of potassium titanate whiskers are dispersed at high speed for 4 hours.

[0067] The difference between Preparation Example 15 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 16.8g spherical alumina, 4.8g ultrafine phlogopite flakes, 2.4g boron nitride nanosheets, 102g chopped ceramic fibers, 20.4g nanocarbon fibers, 81.6g chopped aramid fibers (tensile strength 2900MPa, initial modulus 120GPa, 8mm aramid fiber chopped, Changzhou Yaobang Friction Material Factory), 6g zinc oxide whiskers, and 6g potassium titanate whiskers are dispersed at high speed for 4 hours.

[0068] The difference between Preparation Example 16 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 16.8g of spherical alumina, 4.8g of ultrafine phlogopite flakes, 2.4g of boron nitride nanosheets, 122.4g of chopped ceramic fibers, 20.4g of nano-carbon fibers, 61.2g of chopped aramid fibers, 6g of zinc oxide whiskers, and 6g of potassium titanate whiskers are dispersed at high speed for 4 hours.

[0069] The difference between Preparation Example 17 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 16.8g of spherical alumina, 4.8g of ultrafine phlogopite flakes, 2.4g of boron nitride nanosheets, 173.4g of chopped ceramic fibers, 10.2g of nanocarbon fibers, 20.4g of chopped aramid fibers, 6g of zinc oxide whiskers, and 6g of potassium titanate whiskers are dispersed at high speed for 4 hours.

[0070] The difference between Preparation Example 18 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is configured: 16.8g of spherical alumina, 4.8g of ultrafine phlogopite flakes, 2.4g of boron nitride nanosheets, 122.4g of chopped ceramic fibers, 20.4g of nanocarbon fibers, 61.2g of chopped carbon fibers (product name: K223SE, DIALEAD chopped fibers, length 6mm; carbon fiber type PITCH 65t, Dalian Dongsen Chemical), 6g of zinc oxide whiskers, and 6g of potassium titanate whiskers are dispersed at high speed for 4 hours.

[0071] The difference between Preparation Example 19 and Preparation Example 16 is that the chopped ceramic fibers are composed of 1 mm 3M Nextel 720 ceramic fibers, 5 mm 3M Nextel 720 ceramic fibers, and 10 mm 3M Nextel 720 ceramic fibers in a mass ratio of 1:1:1.

[0072] The difference between Preparation Example 20 and Preparation Example 16 is that the chopped ceramic fibers are composed of 1 mm 3M Nextel 720 ceramic fibers, 5 mm 3M Nextel 720 ceramic fibers, and 10 mm 3M Nextel 720 ceramic fibers in a mass ratio of 1:8:1.

[0073] The difference between Preparation Example 21 and Preparation Example 16 is that the chopped ceramic fibers are composed of 1 mm 3M Nextel 720 ceramic fibers, 5 mm 3M Nextel 720 ceramic fibers, and 10 mm 3M Nextel 720 ceramic fibers in a mass ratio of 2:6:2.

[0074] The difference between Preparation Example 22 and Preparation Example 16 is that the chopped ceramic fibers are composed of 1 mm 3M Nextel 720 ceramic fibers, 5 mm 3M Nextel 720 ceramic fibers, and 10 mm 3M Nextel 720 ceramic fibers in a mass ratio of 1:7:2.

[0075] The difference between Preparation Example 23 and Preparation Example 6 is that the surface modification treatment method of the inorganic filler composition having wear-resistant, toughening and reinforcing effects is as follows:

[0076] Step 1, preparation of composite coupling agent:

[0077] 1 mol of γ-methacryloxypropyltrimethoxysilane KH-570 and 1.02 mol of γ-aminopropyltriethoxysilane KH550 were mixed to obtain a siloxane coupling agent, and 2 g of di(dioctylpyrophosphoryl)ethylene titanate was added to 12 g of the siloxane coupling agent and stirred at 30 rpm for 15 min to obtain a composite coupling agent;

[0078] At the same time, an inorganic filler composition with wear-resistant, toughening and reinforcing effects is prepared: 12g of spherical alumina, 12g of ultrafine phlogopite flakes, 180g of chopped ceramic fibers, 24g of nanocarbon fibers, and 12g of zinc oxide whiskers are dispersed at high speed for 4 hours;

[0079] Step 2: Add the inorganic filler composition with wear-resistant, toughening and reinforcing functions to the grinder, and evenly add the composite coupling agent to the grinder through a quantitative pump. 10 g of the composite coupling agent is added to 100 g of the inorganic filler composition with wear-resistant, toughening and reinforcing functions. Grinding is performed during the addition of the composite coupling agent. After the addition of the composite coupling agent is completed, grinding is continued for 15 minutes to obtain a surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions.

[0080] The difference between Preparation Example 24 and Preparation Example 6 is that the surface modification treatment method of the inorganic filler composition having wear-resistant, toughening and reinforcing effects is as follows:

[0081] Step 1: Prepare an inorganic filler composition with wear-resistant, toughening and reinforcing effects: 12g of spherical alumina, 12g of ultrafine phlogopite flakes, 180g of chopped ceramic fibers, 24g of nanocarbon fibers, and 12g of zinc oxide whiskers are dispersed at high speed for 4 hours;

[0082] Step 2: Add the inorganic filler composition with wear-resistant, toughening and reinforcing functions to the grinder, and evenly add KH-570 to the grinder through a quantitative pump. Add 10 g of KH-570 to 100 g of the inorganic filler composition with wear-resistant, toughening and reinforcing functions. Grind during the addition of the composite coupling agent. After the addition of KH-570 is completed, continue grinding for 15 minutes to obtain a surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions.

[0083] The difference between Preparation Example 25 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is prepared: 50g of spherical alumina and 150g of chopped ceramic fibers are dispersed at high speed for 4 hours.

[0084] The difference between Preparation Example 26 and Preparation Example 6 is that an inorganic filler composition with wear-resistant, toughening and reinforcing effects is prepared: 50g of spherical alumina, 140g of chopped ceramic fibers and 10g of zinc oxide whiskers are dispersed at high speed for 4 hours.

[0085] The difference between Preparation Example 27 and Preparation Example 6 is that the inorganic filler composition having wear-resistant, toughening and reinforcing effects is 200 g of chopped ceramic fibers.

[0086] Example

[0087] A high-strength wear-resistant ABS alloy is prepared from the following raw materials in parts by weight: 70-80 parts of PC resin, 14-20 parts of ABS resin, 4-8 parts of toughening agent, 18-26 parts of inorganic filler composition with wear-resistant, toughening and reinforcing functions, 0.5-2 parts of coupling agent, 0.5-2 parts of dispersant, 3-6 parts of compatibilizer and 0.5-2 parts of anti-aging agent.

[0088] Preferably, the high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 80 parts of PC resin, 18-20 parts of ABS resin, 5-6 parts of toughening agent, 22-24 parts of an inorganic filler composition with wear-resistant, toughening and reinforcing effects, 1-2 parts of a coupling agent, 1-2 parts of a dispersant, 4-6 parts of a compatibilizer, and 1-2 parts of an anti-aging agent.

[0089] The inorganic filler composition with wear-resistant, toughening and reinforcing effects comprises a wear-resistant inorganic filler, a toughening and reinforcing fibrous filler, and a toughening and reinforcing whisker filler in a mass ratio of (8-15):(75-88):(4-10). The wear-resistant inorganic filler is spherical aluminum oxide and / or spherical silicon carbide with at least one of ultrafine mica sheets and boron nitride nanosheets. The toughening and reinforcing fibrous filler is chopped ceramic fiber with at least one of nano-aramid fiber, nano-carbon fiber, and chopped aramid fiber. The toughening and reinforcing whisker filler is zinc oxide whisker and / or potassium titanate whisker.

[0090] Preferably, the inorganic filler composition with wear-resistant, toughening and reinforcing effects comprises a wear-resistant inorganic filler, a toughening and reinforcing fibrous filler and a toughening and reinforcing whisker-like filler in a mass ratio of 10:85:5; the wear-resistant inorganic filler is spherical alumina, ultrafine mica flakes and boron nitride nanosheets in a mass ratio of (70-90):(5-20):(5-10); the toughening and reinforcing whisker-like filler is zinc oxide whisker and potassium titanate whisker in a mass ratio of (40-60):(40-60).

[0091] Preferably, the toughening and reinforcing fibrous filler is composed of chopped ceramic fibers, nanocarbon fibers, and chopped aramid fibers in a mass ratio of (50-85):(5-10):(10-40). The length of the chopped aramid fibers is 0.5-15.0 mm.

[0092] Preferably, the toughening and reinforcing fibrous filler is composed of chopped ceramic fibers, nano-aramid fibers, and chopped carbon fibers in a mass ratio of (50-85):(5-10):(10-40). The length of the chopped carbon fibers is 0.5-8.0 mm.

[0093] Further preferably, the mass ratio of the chopped ceramic fibers with a length of 0.5-2.0 mm, the chopped ceramic fibers with a length of 4-8 mm, and the chopped ceramic fibers with a length of 10-15 mm in the chopped ceramic fibers is (10-20):(60-80):(10-20).

[0094] The toughening agent is TPU resin, and the polyol in the raw material for preparing the TPU resin contains terminal hydroxyl polybutadiene. Preferably, the toughening agent TPU resin includes diisocyanate, small molecule diol chain extender, polyol, catalyst, wear-resistant filler, leveling agent, antioxidant, and ultraviolet absorber. The total molar amount of active functional groups contained in the chain extender and polyol is equal to 1.0-1.02 times the molar amount of -NCO in the diisocyanate. The hard segment content in the TPU resin is 45-50wt%. The diisocyanate is an aromatic diisocyanate or a composition of an aromatic diisocyanate and an aliphatic diisocyanate. The small molecule diol chain extender is at least one of 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,4-butanediamine, and 1,6-hexanediamine. The polyol is composed of terminal hydroxyl polybutadiene with a molecular weight of 500-2000, polycaprolactone hexamethylene glycol with a molecular weight of 1000-2000, and hydroxyl-terminated methyl vinyl silicone oil with a vinyl content of 6-8 mol% in a mass ratio of (10-30): (60-85): (5-10). The catalyst is organic tin or organic bismuth. The wear-resistant filler content in the TPU resin is 2-4wt%. The wear-resistant filler is at least one of nano-alumina, nano-zirconium oxide, and nano-tungsten carbide.

[0095] The coupling agent is a siloxane and / or a titanate coupling agent. Preferably, the coupling agent is composed of a siloxane coupling agent and a titanate coupling agent in a mass ratio of (80-90):(10-20); the siloxane coupling agent includes methacryloxysilane and aminosilane, which are prepared by reflux reaction at 70-90°C for 2-4h; the titanate coupling agent is di(dioctylpyrophosphoryl)ethylene titanate and / or di(dioctylpyrophosphoryl)oxyacetyl peptide.

[0096] The dispersant is stearate, and the specific dispersant is zinc stearate.

[0097] The compatibilizer is ABS-g-MAH and / or styrene-grafted maleic anhydride multipolymer, preferably ABS-g-MAH.

[0098] The antioxidant is composed of an antioxidant and an anti-ultraviolet agent in a mass ratio of (1-2):(1-2). The antioxidant is composed of an antioxidant and an anti-ultraviolet agent in a mass ratio of (1.4-1.6):(0.8-1.2). The antioxidant is at least one of nano silicon nitride, nano silicon dioxide, and nano titanium nitride, and is combined with antioxidant 1098 and antioxidant 168. The anti-ultraviolet agent is at least one of UV-531, UV-326, UV-327, UV-328, UV-329, UV-234, and UV-770.

[0099] A method for preparing a high-strength wear-resistant ABS alloy comprises the following steps:

[0100] Step 1: Preparation of an inorganic filler composition having wear-resistant, toughening and reinforcing effects and preparation of a toughening agent;

[0101] Step 2: using a coupling agent to perform surface modification treatment on the inorganic filler composition having wear-resistant, toughening and reinforcing effects;

[0102] Step three, the accurately measured PC resin, ABS resin, toughening agent, surface modified inorganic filler composition with wear-resistant toughening and reinforcing effect, coupling agent, dispersant, compatibilizer and antioxidant are mixed at high speed and then put into a twin-screw extruder, and melt extrusion is carried out at an extrusion temperature of 245-255°C and a screw speed of 300-500rpm. The obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain PC / ABS alloy masterbatch material.

[0103] Example 1: A high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 70 parts of PC resin (SURLYN PC2000 DuPont, USA, tensile strength 14Mpa, elongation at break 760%, melt flow rate 4.5g / 10min), 15 parts of ABS resin (Chimei PA-709, Ningbo Rongsu New Materials Co., Ltd.), 4 parts of the toughening agent in Preparation Example 1, 14 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 6, 0.8 parts of zinc stearate, 4 parts of compatibilizer-ABS-g-MAH (Foshan Zuogao Plastic Co., Ltd. G1606, ABS-G-MAH maleic anhydride grafted PC alloy compatibilizer), 0.5 parts of nano silicon nitride (4N flaky high-purity nano silicon nitride powder, average particle size 50-200 nanometers, Hebei Wenlun Metal Materials Co., Ltd.), 0.8 parts of antioxidant 1098, 0.1 parts of antioxidant 168, 0.4 parts of UV-531, and 0.2 parts of UV-770.

[0104] A method for preparing a high-strength wear-resistant ABS alloy comprises the following steps:

[0105] Step 1: Preparation of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects, see Preparation Example 6;

[0106] The preparation of toughening agent TPU is shown in Preparation Example 1;

[0107] Step 2, the accurately measured PC resin, ABS resin, toughening agent TPU in Preparation Example 1, the surface-modified inorganic filler composition with wear-resistant toughening and reinforcing effect in Preparation Example 6, dispersant-zinc stearate, compatibilizer-ABS-g-MAH, nano silicon nitride, antioxidant 1098, antioxidant 168, UV-531, UV-770 are mixed at high speed and uniformly put into a twin-screw extruder, and melt extrusion is carried out at an extrusion temperature of 250°C. The seven heating zones of the twin-screw extruder are set to the following temperatures: 200°C for zone 1, 220°C for zone 2, 235°C for zone 3, 245°C for zone 4, 250°C for zone 5, 250°C for zone 6, and 250°C for zone 7. The screw speed is 320rpm, and the obtained molten extruded material is subjected to wire drawing cooling, granulation, and drying to obtain a PC / ABS alloy masterbatch material with a particle size of 2.4-2.6mm.

[0108] The difference between Example 2 and Example 1 is that a high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 70 parts of PC resin, 18 parts of ABS resin-Chimei PA-709, 5 parts of the toughening agent TPU resin in Preparation Example 1, 16 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 7, 1.2 parts of zinc stearate, 5 parts of compatibilizer-ABS-g-MAH, 0.5 parts of nano-silicon nitride, 0.8 parts of antioxidant 1098, 0.1 parts of antioxidant 168, 0.4 parts of UV-531, and 0.2 parts of UV-770.

[0109] The difference between Example 3 and Example 1 is that a high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 80 parts of PC resin, 20 parts of ABS resin-Chimei PA-709, 6 parts of the toughening agent TPU resin in Preparation Example 1, 20 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8, 1.5 parts of zinc stearate, 6 parts of compatibilizer-ABS-g-MAH, 0.5 parts of nano-silicon nitride, 0.8 parts of antioxidant 1098, 0.1 parts of antioxidant 168, 0.4 parts of UV-531, and 0.2 parts of UV-770.

[0110] The difference between Example 4 and Example 3 is that the toughening agent TPU resin in Preparation Example 1 is replaced by the toughening agent TPU resin in Preparation Example 2.

[0111] The difference between Example 5 and Example 3 is that the toughening agent TPU resin in Preparation Example 1 is replaced by the toughening agent TPU resin in Preparation Example 3.

[0112] The difference between Example 6 and Example 3 is that the toughening agent TPU resin in Preparation Example 1 is replaced by the toughening agent TPU resin in Preparation Example 4.

[0113] The difference between Example 7 and Example 3 is that the toughening agent TPU resin in Preparation Example 1 is replaced by the toughening agent TPU resin in Preparation Example 5.

[0114] The difference between Example 8 and Example 3 is that the toughening agent TPU resin in Preparation Example 1 is replaced by BASF 1160DTPU resin.

[0115] The difference between Example 9 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 9.

[0116] The difference between Example 10 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 10.

[0117] The difference between Example 11 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 11.

[0118] The difference between Example 12 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 12.

[0119] The difference between Example 13 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 13.

[0120] The difference between Example 14 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 14.

[0121] The difference between Example 15 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 15.

[0122] The difference between Example 16 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 16.

[0123] The difference between Example 17 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 17.

[0124] The difference between Example 18 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 18.

[0125] The difference between Example 19 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 19.

[0126] The difference between Example 20 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 20.

[0127] The difference between Example 21 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 21.

[0128] The difference between Example 22 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions in Preparation Example 22.

[0129] Comparative Example

[0130] The difference between Comparative Example 1 and Example 1 is that a high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 65 parts of PC resin, 20 parts of ABS resin-Chimei PA-709, 4 parts of the toughening agent TPU resin in Preparation Example 1, 12 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 6, 1.2 parts of zinc stearate, 4 parts of compatibilizer-ABS-g-MAH, 0.5 parts of nano-silicon nitride, 0.8 parts of antioxidant 1098, 0.1 parts of antioxidant 168, 0.4 parts of UV-531, and 0.2 parts of UV-770.

[0131] The difference between Comparative Example 2 and Example 1 is that a high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 100 parts of PC resin, 25 parts of ABS resin-Chimei PA-709, 5 parts of the toughening agent TPU resin in Preparation Example 1, 20 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 6, 1.5 parts of zinc stearate, 6 parts of compatibilizer-ABS-g-MAH, 0.5 parts of nano-silicon nitride, 0.8 parts of antioxidant 1098, 0.1 parts of antioxidant 168, 0.4 parts of UV-531, and 0.2 parts of UV-770.

[0132] The difference between Comparative Example 3 and Example 3 is that a high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 80 parts of PC resin, 20 parts of ABS resin-Chimei PA-709, 20 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8, 1.5 parts of zinc stearate, 6 parts of compatibilizer-ABS-g-MAH, 0.5 parts of nano-silicon nitride, 0.8 parts of antioxidant 1098, 0.1 parts of antioxidant 168, 0.4 parts of UV-531, and 0.2 parts of UV-770.

[0133] The difference between Comparative Example 4 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 23.

[0134] The difference between Comparative Example 5 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 24.

[0135] The difference between Comparative Example 6 and Example 3 is that a high-strength wear-resistant ABS alloy is made of the following raw materials in parts by weight: 80 parts of PC resin, 20 parts of ABS resin-Chimei PA-709, 6 parts of the toughening agent TPU resin in Preparation Example 1, 20 parts of the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8, 1.5 parts of zinc stearate, 6 parts of compatibilizer-ABS-g-MAH, 1 part of antioxidant 1098, 0.2 parts of antioxidant 168, and 0.8 parts of UV-531.

[0136] The difference between Comparative Example 7 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing effects in Preparation Example 25.

[0137] The difference between Comparative Example 8 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions in Preparation Example 26.

[0138] The difference between Comparative Example 9 and Example 3 is that the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions in Preparation Example 8 is replaced by the surface-modified inorganic filler composition with wear-resistant, toughening and reinforcing functions in Preparation Example 27.

[0139] Performance testing

[0140] 1. Test method for tensile strength and elongation at break: Determine according to the test method of GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics".

[0141] 2. Notched impact strength test method: Test according to the cantilever beam impact strength test in accordance with GB / T 1843-2010.

[0142] 3. Bending strength test method: Test in accordance with GB / T 9341-2008 "Determination of flexural properties of plastics".

[0143] 4. Wear resistance test method: Determined in accordance with GBT 3960-2016 "Plastic sliding friction and wear test method".

[0144] Data analysis

[0145] Table 1 is a table of test parameters of ABS alloy materials in Examples 1-26 and Comparative Examples 1-9

[0146]

[0147]

[0148] It can be seen from Examples 1-26 and Comparative Examples 1-9 and Table 1 that the inorganic filler composition formed by compounding the wear-resistant inorganic filler, the toughening and reinforcing fibrous filler, and the toughening and reinforcing whisker filler in the present invention combined with the special TPU toughening agent gives the ABS alloy material good anti-aging performance, wear resistance, and mechanical strength while also having good impact toughness and low-temperature resistance, solving the problem of large residual stress during molding and easy stress cracking of the product.

[0149] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A high-strength wear-resistant ABS alloy, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of PC resin, 14-20 parts of ABS resin, 4-8 parts of toughening agent, 18-26 parts of inorganic filler composition with wear-resistant, toughening and reinforcing effects, 0.5-2 parts of coupling agent, 0.5-2 parts of dispersant, 3-6 parts of compatibilizer and 0.5-2 parts of anti-aging agent; The inorganic filler composition with wear-resistant, toughening and reinforcing effects comprises a wear-resistant inorganic filler, a toughening and reinforcing fibrous filler, and a toughening and reinforcing whisker filler in a mass ratio of (8-15):(75-88):(4-10); The wear-resistant inorganic filler is at least one of spherical alumina and / or spherical silicon carbide combined with ultrafine mica flakes and boron nitride nanosheets; The toughening and reinforcing fibrous filler is at least one of chopped ceramic fibers combined with nano-aramid fibers, nano-carbon fibers, and chopped aramid fibers; The toughening and reinforcing whisker-like filler is zinc oxide whisker and / or potassium titanate whisker; The toughening agent is TPU resin; The dispersant is stearate; The compatibilizer is ABS-g-MAH and / or styrene-grafted maleic anhydride multipolymer; The TPU resin includes diisocyanate, small molecule diol chain extender, polyol, catalyst, wear-resistant filler, leveling agent, antioxidant and ultraviolet absorber; The total molar amount of the active functional groups contained in the chain extender and the polyol is equal to 1.0-1.02 times the molar amount of -NCO in the diisocyanate; The hard segment content in the TPU resin is 45-50wt%; The diisocyanate is an aromatic diisocyanate or a combination of an aromatic diisocyanate and an aliphatic diisocyanate; The small molecule diol chain extender is at least one of 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,4-butanediamine, and 1,6-hexanediamine; The polyol is composed of hydroxy-terminated polybutadiene with a molecular weight of 500-2000, polycarbonate diol with a molecular weight of 1000-2000, and hydroxy-terminated methyl vinyl silicone oil with a vinyl content of 6-8 mol% in a mass ratio of (10-30):(60-85):(5-10); The catalyst is organic tin or organic bismuth; the wear-resistant filler content in the TPU resin is 2-4wt%; The wear-resistant filler is at least one of nano-alumina, nano-zirconium oxide and nano-tungsten carbide; The coupling agent is composed of a siloxane coupling agent and a titanate coupling agent in a mass ratio of (80-90):(10-20); the siloxane coupling agent comprises methacryloxysilane and aminosilane, which are prepared by reflux reaction at 70-90° C. for 2-4 hours; the titanate coupling agent is di(dioctylpyrophosphoryl)ethylene titanate and / or di(dioctylpyrophosphoryl)oxyacetyl peptide; The antioxidant is composed of an antioxidant and an anti-ultraviolet agent in a mass ratio of (1.4-1.6):(0.8-1.2); the antioxidant is at least one of nano silicon nitride, nano silicon dioxide, and nano titanium nitride, and is combined with antioxidant 1098 and antioxidant 168; the anti-ultraviolet agent is at least one of UV-531, UV-326, UV-327, UV-328, UV-329, UV-234, and UV-770.

2. The high-strength wear-resistant ABS alloy according to claim 1, characterized in that: The high-strength wear-resistant ABS alloy comprises the following raw materials in parts by weight: 80 parts of PC resin, 18-20 parts of ABS resin, 5-6 parts of toughening agent, 22-24 parts of inorganic filler composition with wear-resistant, toughening and reinforcing functions, 1-2 parts of coupling agent, 1-2 parts of dispersant, 4-6 parts of compatibilizer and 1-2 parts of anti-aging agent.

3. A high-strength wear-resistant ABS alloy according to claim 1 or 2, characterized in that: The inorganic filler composition with wear-resistant, toughening and reinforcing effects comprises a wear-resistant inorganic filler, a toughening and reinforcing fibrous filler and a toughening and reinforcing whisker filler in a mass ratio of 10:85:5; the wear-resistant inorganic filler is spherical aluminum oxide, ultrafine mica flakes and boron nitride nanosheets in a mass ratio of (70-90):(5-20):(5-10); the toughening and reinforcing whisker filler is zinc oxide whisker and potassium titanate whisker in a mass ratio of (40-60):(40-60).

4. The high-strength wear-resistant ABS alloy according to claim 3, characterized in that: The toughening and reinforcing fibrous filler is composed of chopped ceramic fibers, nanocarbon fibers, and chopped aramid fibers in a mass ratio of (50-85):(5-10):(10-40); the chopped ceramic fibers include chopped ceramic fibers with a length of 0.5-2.0 mm, chopped ceramic fibers with a length of 4-8 mm, and chopped ceramic fibers with a length of 10-15 mm; the length of the chopped aramid fibers is 0.5-15 mm.

5. The high-strength and wear-resistant ABS alloy according to claim 3, characterized in that: The toughening and reinforcing fibrous filler is composed of chopped ceramic fibers, nano-aramid fibers, and chopped carbon fibers in a mass ratio of (50-85):(5-10):(10-40); the chopped ceramic fibers include chopped ceramic fibers with a length of 0.5-2.0 mm, chopped ceramic fibers with a length of 4-8 mm, and chopped ceramic fibers with a length of 10-15 mm; the length of the chopped carbon fibers is 0.5-8.0 mm.

6. A high-strength wear-resistant ABS alloy according to claim 4 or 5, characterized in that: The chopped ceramic fibers have a length of 0.5-2.0 mm, a length of 4-8 mm, and a length of 10-15 mm, and the mass ratio of the chopped ceramic fibers is (10-20):(60-80):(10-20).

7. A method for preparing the high-strength wear-resistant ABS alloy according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Preparation of an inorganic filler composition having wear-resistant, toughening and reinforcing effects and preparation of a toughening agent; Step 2: using a coupling agent to perform surface modification treatment on the inorganic filler composition having wear-resistant, toughening and reinforcing effects; Step three, the accurately measured PC resin, ABS resin, toughening agent, surface modified inorganic filler composition with wear-resistant toughening and reinforcing effect, coupling agent, dispersant, compatibilizer and antioxidant are mixed at high speed and evenly put into a twin-screw extruder, and melt extrusion is carried out at an extrusion temperature of 245-255°C and a screw speed of 300-500rpm. The obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain a high-strength and wear-resistant ABS alloy.

Citation Information

Patent Citations

  • High-performance mineral-filled PC / ABS alloy material and preparation method thereof

    CN104387740A

  • Highly-wear-resistant silicon nitride / polyformaldehyde nano composite material and preparation method thereof

    CN105670214A